In situ sampling to determine the volumetric weight and natural moisture of the coal - Ahmeti, Hysen (Wroclaw University of Technology, 2025)
The ongoing energy crisis highlights the urgent need to utilize coal from existing power plants for electricity generation. The exploitation of geological coal reserves in the Sibovci mine is influenced by the terrain configuration, particularly the roof and floor layers of the coal seam. This paper presents a meth-odology for coal sampling in the field and laboratory analysis to determine calorific value, bulk density, and natural moisture content. These parameters are crucial for ensuring both geotechnical safety and envi-ronmental protection during coal extraction and transportation. The study involved collecting 172 samples from the open coal seam profile, from an elevation range of 550 m to 650 m, using a modified drilling de-vice. The samples were analyzed to determine the average values, variance, and distribution of bulk density and natural moisture content. Additionally, correlation analysis was conducted between the two parame-ters. This research helps optimize the combustion and transportation process, reducing environmental impacts such as air, water, and soil pollution. Furthermore, the findings have been applied in designing excavation slopes, contributing to improved stability and safety during coal extraction in the Sibovci mine. The study also aids in minimizing the environmental footprint of coal exploitation, ensuring that it aligns with established standards for sustainable energy production.
Mining Science, Vol. 32, 2025, s. 31-45
Keywords: mining; geology; geo-engineering